2011
DOI: 10.1590/s0103-50532011001100020
|View full text |Cite
|
Sign up to set email alerts
|

Dual bifunctional catalysis and the α-effect in the reaction of hydroxylamine with phenylacetate

Abstract: A reação da hidroxilamina com acetato de fenila foi investigada teoricamente para se obter uma melhor compreensão do efeito alfa nas reações de nucleófilos neutros. Os cálculos foram feitos em nível B3LYP/6-311+G(2df,2p)//HF/6-31G(d) incluindo o solvente (água) em nível PCM/HF/6-31G(d). Os resultados mostram que um ataque direto da hidroxilamina leva a uma barreira de energia livre de ativação DG ‡ muito alta, em torno de 50 kcal mol -1. Uma segunda molécula de hidroxilamina pode catalisar o processo através d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Our previous report has indicated that explicit water molecules can facilitate the hydroxylamine attack to the carboxylic ester. 4 We can notice that the overall kinetic barriers (theoretical and experimental) differ by only 1.3 kcal mol −1 , while the relative barriers are 1.5 kcal mol −1 (theoretical) and 1.9 kcal mol −1 (experimental). Furthermore, the special structure of the tetrahedral intermediates like MS1b and MS2 suggests that -OH and -NH 2 groups can act more efficiently than explicit water, because no entropic cost will be involved.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Our previous report has indicated that explicit water molecules can facilitate the hydroxylamine attack to the carboxylic ester. 4 We can notice that the overall kinetic barriers (theoretical and experimental) differ by only 1.3 kcal mol −1 , while the relative barriers are 1.5 kcal mol −1 (theoretical) and 1.9 kcal mol −1 (experimental). Furthermore, the special structure of the tetrahedral intermediates like MS1b and MS2 suggests that -OH and -NH 2 groups can act more efficiently than explicit water, because no entropic cost will be involved.…”
Section: Resultsmentioning
confidence: 82%
“…5 However, the barrier is very high and not competitive. Our previous report has indicated that explicit water molecules can facilitate the hydroxylamine attack to the carboxylic ester.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Possible mechanisms of the ring formation are described and discussed in the literature in detail. [36][37][38] Biochemical testing of the novel fragments revealed an overall improvement of binding affinity along with convincing ligand efficiency: 30 a (K i = 930 mm), 30 b (K i = 315 mm), and 30 c 33 n.i. (K i = 128 mm), with ligand efficiencies of 0.32 kcal, 0.34 kcal, and 0.36 kcal, respectively ( Table 2).…”
Section: Hit Optimizationmentioning
confidence: 99%